АҚМОЛА ОБЛЫСЫ ЖАҒДАЙЫНДА СУБКЛИНИКАЛЫҚ МАСТИТ КЕЗІНДЕ СИЫРЛАРДЫҢ ҚАНЫНЫҢ БИОХИМИЯЛЫҚ ЖӘНЕ МОРФОЛОГИЯЛЫҚ КӨРСЕТКІШТЕРІ - Г. Мержақыпова; Ж. Кемешов; А. Карамян; А. Бакбергенова; Ғ. Ергешбаева; А. Өмірәлі (Animal Health and Biosafety, 2026)
Subclinical mastitis is one of the most common diseases in dairy cattle breeding and leads to significant economic losses. Its main difficulty is that the disease passes for a long time without pronounced clinical symptoms. During this period, inflammation develops in the udder tissue, the quality and productivity of milk begins to decrease, and changes in metabolism and immune response are formed in the body. Therefore, additional laboratory indicators that allow early detection of the disease are increasing in importance. The purpose of the study is to assess biochemical and morphological changes in the blood of cows with subclinical mastitis in the conditions of Enbek LLP in Akmola region. The study was conducted in 2025-2026. 12 lactating cows were introduced into the experiment and two groups were formed on the principle of pairs-analogues: clinically healthy cows (n=6) and cows with subclinical mastitis (n=6). To determine the disease, the Californian mastitis test and indicator express methods were used. Morphological indicators of blood and biochemical indicators of blood serum were studied. In animals in which subclinical mastitis was detected, it was found that the activity of Total Protein, urea, total bilirubin and alkaline phosphatase increased, and glucose and calcium levels decreased. At the same time, there was a tendency to decrease the indicators of red blood cells, hemoglobin and hematocrit, and an increase in the number of white blood cells was the most obvious sign of an inflammatory reaction. The results obtained showed that with subclinical mastitis, systemic changes are formed in the body. A comprehensive assessment of biochemical and morphological blood indicators together with the results of a milk study will allow early detection of the disease, timely treatment measures and reduce economic losses in dairy farms.